2000
DOI: 10.1002/1097-0215(20001101)88:3<464::aid-ijc20>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of γ-glutamyltransferase in cisplatin-resistant and -sensitive colon carcinoma cells after acute cisplatin and oxidative stress exposures

Abstract: Glutathione plays an important role in drug resistance of tumor cells and in their ability to resist oxidative stress. Improved salvage of glutathione can be obtained through increased activity of γ‐glutamyltransferase (GGT), which is of importance in the maintenance of cellular glutathione homeostasis. We investigated the regulation of GGT in 2 cisplatin‐resistant and 1 cisplatin‐sensitive colon carcinoma cell lines. Enzyme activity was induced in all 3 cell lines after acute exposure to cisplatin. The elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The significant positive correlation (r = 0.27, p<0.05) between uric acid and GGT in the exposed group, supports earlier hypothesis that GGT may in part be a marker of oxidative stress. It has been demonstrated that primary human memory T cells expressed higher level of GGT than native T cells (Borud et al, 2000;Mikkelsen et al, 2002). This observation suggests that increased GGT expression may provide an adaptive advantage in permitting these cells to resist oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant positive correlation (r = 0.27, p<0.05) between uric acid and GGT in the exposed group, supports earlier hypothesis that GGT may in part be a marker of oxidative stress. It has been demonstrated that primary human memory T cells expressed higher level of GGT than native T cells (Borud et al, 2000;Mikkelsen et al, 2002). This observation suggests that increased GGT expression may provide an adaptive advantage in permitting these cells to resist oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to be in agreement with the findings of Corti et al (2010) and Singh et al (2011) that GGT provides pre-neoplastic cells with resistance to acute toxicity of carcinogens owing to its participation in phase-II detoxification of xenobiotics. Several lines of evidence indicate that the advantage may be provided by the ability of GGT to retrieve GSH constituents, which leads to increased cellular GSH or replenishment of GSH (Borud et al, 2000;Mikkelsen et al, 2002). The study of Lee et al (2004) has shown that cellular GGT catalyses the first step in degradation of extracellular glutathione.…”
Section: Resultsmentioning
confidence: 99%
“…GGT plays a pivotal role in the extracellular catabolism of glutathione, a powerful antioxidant, and is upregulated in response to oxidative stress in epithelial and cancer cells. Accordingly, the transcription of GGT is increased after exposure to oxidants [23,24]. It has been suggested that elevation of GGT is an adaptive response of cancer cells for protection against oxidative stress [25].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been shown to induce γGT expression (Kugelman et al, 1994; Knickelbein et al, 1996; Liu et al, 1998; Borud et al, 2000; Roomi et al, 2006). High γGT expression protects melanoma cells from hydrogen peroxide or ascorbic acid induced oxidative stress (Giommarelli et al, 2008).…”
Section: Glutathione S-derivatives Activated By γGt and Peptidasesmentioning
confidence: 99%